Histopathologic subtype of hippocampal sclerosis and episodic memory performance before and after temporal lobectomy for epilepsy. (14th March 2018) - Saghafi, Shahram; Ferguson, Lisa; Hogue, Olivia; Gales, Jordan M.; Prayson, Richard; Busch, Robyn M.
Summary: Objective: The International League Against Epilepsy (ILAE) proposed a classification system for hippocampal sclerosis (HS) based on location and extent of hippocampal neuron loss. The literature debates the usefulness of this classification system when studying memory in people with temporal lobe epilepsy (TLE) and determining memory outcome after temporal lobe resection (TLR). This study further explores the relationship between HS ILAE subtypes and episodic memory performance in patients with TLE and examines memory outcomes after TLR. Methods: This retrospective study identified 213 patients with TLE who underwent TLR and had histopathological evidence of HS (HS ILAE type 1a = 92; type 1b = 103; type 2 = 18). Patients completed the Wechsler Memory Scale—3rd Edition prior to surgery, and 78% of patients had postoperative scores available. Linear regressions examined differences in preoperative memory scores as a function of pathology classification, controlling for potential confounders. Fisher's exact tests were used to compare pathology subtypes on the magnitude of preoperative memory impairment and the proportion of patients who experienced clinically meaningful postoperative memory decline. Results: Individuals with HS ILAE type 2 demonstrated better preoperative verbal memory performance than patients with HS ILAE type 1; however, individual data revealed verbal and visual episodic memory impairments in many patients with HS ILAE type 2. The base rate of postoperative memory decline was similar among all 3 pathology groups. Significance: This is the largest reported overall sample and the largest subset of patients with HS ILAE type 2. Group data suggest that patients with HS ILAE type 2 perform better on preoperative memory measures, but individually there were no differences in the magnitude of memory impairment. Following surgery, there were no statistically significant differences between groups in the proportion of patients who declined. Future research should focus on quantitative measurements of hippocampal neuronal loss, and multicenter collaboration is encouraged.